Spectrums of neurological manifestations of COVID-19 in children and its immediate and long term outcome: Experience of the largest pediatric COVID unit of Bangladesh (Bangladesh Journal of Child Health, 2025)
Background: SARS Cov-2 infection presented with mild respiratory illness but has evidence of multisystem involvement in little percentage, though severity of infection is less in children. Neurological manifestations may vary from headache, dizziness, olfactory or taste dysfunction to specific syndromes including meningitis, stroke, acute transverse myelitis, ADEM and Guillain-Barre syndrome. But there is little evidence worldwide about neurological complications of COVID-19 in children. Methods: This longitudinal study was carried out in COVID unit of Dhaka medical college among the children age 1 month to 14 years, who were positive for covid-19 RT-PCR and presented with neurological features with further follow up for a period of 6 months. Results: Among 539 COVID confirmed cases 53 (9.83%) were presented with neurological manifestations; mean age of the patient’s was 64.09±43.09 months with male predominance. Among the studied population 35(66%) cases presented with features of meningoencephalitis, 6(11.3%) with febrile seizures, 4(5.6%) with GBS. Acute stroke syndrome, transeverse myelitis, ADEM and autoimmune encephalitis 2(3.8%) cases from each. Three (7.5%) cases expired. At the end of follow up only 3 cases found with neurological complications, one with epilepsy and two had residual motor weakness. Conclusion: Neurological involvement of COVID-19 in children is not uncommon, early suspicion and intervention is crucial to limit the mortality and morbidity.BANGLADESH J CHILD HEALTH 2023; VOL 47 (3) : 150-156